The Essence of Ridha: Ibn Qayyim al-Jauziyah's Views on Spiritual Fulfillment and Divine Acceptance - Saputra, Aris; Ermagusti, Ermagusti; Efendi, Efendi (Islamic Thought Review, 2024)
This paper investigates the Islamic philosophical and theological concept of ridha as elucidated by the prominent scholar Ibn Qayyim Al-Jauziyah. Ridha, in Ibn Qayyim’s view, represents a state of inner tranquility and acceptance, essential for mitigating anxiety and dissatisfaction in individuals. Despite the material wealth prevalent in contemporary society, many still experience spiritual unrest due to a lack of ridha. This study posits that true belief in God necessitates a serene acceptance of divine provisions, embracing both adversities and blessings with contentment. The research employs a qualitative approach, utilizing library research and descriptive analysis of relevant literature to provide a comprehensive understanding of ridha. Content analysis techniques are applied to systematically evaluate and interpret the concept and its implications. Findings reveal that for Ibn Qayyim, ridha involves a profound acceptance of Allah’s will, characterized by the absence of discontent towards divine decrees and a balanced approach to both favorable and adverse circumstances. The study delineates three progressive stages of ridha: reconciling with one's situation, fostering harmonious relationships with others, and overcoming envy. This exploration underscores the enduring relevance of ridha in addressing modern existential challenges and spiritual fulfillment.